2019
DOI: 10.1002/jor.24224
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the chondrogenic differentiation of mesenchymal stem cells and cartilage repair by ghrelin

Abstract: Transforming growth factor beta (TGF‐β) is commonly utilized in chondrogenic differentiation protocols, but this often results in incomplete maturation of the derived chondrocytes. Gene expression analysis, quantitation of sulfated glycosaminoglycan and collagen, and histological staining were performed to assess the effects of ghrelin. The signaling pathways involved were investigated with inhibitors or targeted by shRNAs. Joint cavity delivery of TGF‐β with or without ghrelin, within a rat cartilage defect m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Instead of being cultured as in other studies, the cell concentrates containing MSCs were injected into the joint cavity directly during arthroscopy surgery. It is widely believed that culture microenvironment can affect the differentiation of MSCs [27,28,[42][43][44][45][46], and the culturing process can add the risk of infection. According to the studies, it is known that the proliferation and differentiation of MSCs can be influenced by the paracrine effects of the cytokines and growth factors released by the grafted cells, which can trigger host-associated signaling pathways, increase angiogenesis, and decrease apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of being cultured as in other studies, the cell concentrates containing MSCs were injected into the joint cavity directly during arthroscopy surgery. It is widely believed that culture microenvironment can affect the differentiation of MSCs [27,28,[42][43][44][45][46], and the culturing process can add the risk of infection. According to the studies, it is known that the proliferation and differentiation of MSCs can be influenced by the paracrine effects of the cytokines and growth factors released by the grafted cells, which can trigger host-associated signaling pathways, increase angiogenesis, and decrease apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The lowest tested dose of 1 nM ghrelin significantly increased the gene expression levels of SOX9, COL II and ACAN. Ghrelin at other concentrations had a weaker synergistic effect on chondrogenic differentiation [ 13 ]. In this study, we continued to explore the effect of the combination of lower concentrations of ghrelin (1, 0.1 and 0.01 nM) and TGF-β3 (10 ng/mL and 1 ng/mL) on chondrogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin is a polypeptide hormone mainly derived from the stomach and is the first endogenous ligand of growth hormone secretagogue receptor-1a (GHSR-1A) discovered so far [ 12 ]. We just found that ghrelin significantly enhances chondrogenic differentiation both in vitro and in vivo in conjunction with TGF-β3 [ 13 ]. Although hydrogels can deliver growth factors, the hydrophilicity of hydrogels makes the release of hydrophilic molecules too fast.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of being cultured like other research, cell concentrates containing MSCs were injected into the corresponding joint cavity directly during the arthroscopy surgery. It is widely believed that local microenvironment during culture can affect the differentiation of MSCs [27,28,[42][43][44][45][46], and the culturing process can add the risk of infection. According to the studies, it is known that the proliferation and differentiation of MSCs can be in uenced by the paracrine effects of the cytokines and growth factors released by the grafted cells, which can trigger host-associated signaling pathways, increase angiogenesis, and decrease apoptosis.…”
Section: Discussionmentioning
confidence: 99%